BIOLOGICAL STUDIES OF CONYZA AND EUPHORBIA SPECIES - Chaudhry, Bashir Ahmad; Janbaz, Khalid Hussain; Uzair, Muhammad; Ejaz, Abdul Subhan (Journal of Research (Science), 2001)
As a part of our research programme into the exploitation of natural plant sources for their biological activities, we have studied three species namely Conyza bonariensis (Compositae), Euphorbia prostrata and Euphorbia helioscopia (Euphorbiaceae). The arial parts of each species were extracted successively with petroleum ether, dichloromethane and methanol. In the biological screening, brine shrimp toxicity was observed in petroleum ether extracts of all the three species. Dichloromethane extract of E. prostrata and methanol extract of C. bonariensis displayed significant antifungal activity against Cladosporium cucumerinum. Dichloromethane and methanol extracts of C. bonariensis and methanol extract of E. helioscopia showed antibacterial activity against Sarcina leutea. Cholinergic activity was observed in the methanol extract of E. prostrata as well as in the dichloromethane and methanol extracts of C. bonariensis.